Tanggulangi Stunting: Edukasi Kesehatan pada Ibu Hamil, Ibu Menyusui dan Ibu Balita di Nagari Parit, Pasaman Barat - Welly Femelia; Idral Purnakarya (Warta Pengabdian Andalas, 2020)
Nutritional problems occur in almost all age groups including children. Pasaman Barat district is one of the stunting focus locations in West Sumatra with an incidence rate of 32.09% Therefore this community service held in Pasaman Barat District. This health promotion activity aimed to increase mother’s knowledge and skill to overcome stunting incident on children. Method used in this activity is counseling and demonstration. Health promotion was attended by 45 women of childbearing age consisting of 15 pregnant women, nursing mothers and toddler mothers each. Counseling held separately for each group meanwhile in the demonstration session all of participants were joining together to compete on making the nutritious supplementary food. This activity succeeded in having a positive impact on the target group. This can be seen from the enthusiasm of the target in participating at each stage of the activity and in discussion session. The activity was closed by making a commitment to follow up the activity together with the district health office, Parit Primary Health Care and Parit Village party.